Exploring the Entrepreneurial Intentions of Women in the Context of Digital Entrepreneurship Ecosystem - Jonathan Gano-an; Gloria P Gempes (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
The presence of women entrepreneurs in the digital marketplace revolutionizes the way we construct our understanding of entrepreneurship way back. Perhaps, this argument could lead to a better impression that entrepreneurship was once a male-dominated profession. This study was designed to generate a causal model on entrepreneurial intention among women entrepreneurs in the context of entrepreneurial opportunity, alertness, and motivation. A mixed methods design, particularly an explanatory sequential approach, was utilized, and a total of 423 women digital entrepreneurs in the Davao Region participated in this research. Structural equation modeling was utilized to test the hypothesized causal model. Findings indicated that entrepreneurial motivation significantly influences alertness, opportunity, and intention; alertness influences opportunity, but entrepreneurial alertness and entrepreneurial opportunity have no significant influence on entrepreneurial intention. Generally, the structural equation modeling described 67% of the aggregate variance in entrepreneurial intentions, which was statistically significant. The quantitative results were validated by the informants in the qualitative phase. As to the generated model, the informants concurred with the focal role of entrepreneurial motivation in women's entrepreneurial intentions. The emerging themes: personal will, entrepreneurial screening and seizing, social media presence, and stakeholder support substantiated the results in the model. This leads to connecting-merging-confirmation as the nature of integration.